2021
DOI: 10.3389/fcell.2021.733270
|View full text |Cite
|
Sign up to set email alerts
|

The Versatile Roles of Cancer-Associated Fibroblasts in Colorectal Cancer and Therapeutic Implications

Abstract: The tumor microenvironment (TME) is populated by abundant cancer-associated fibroblasts (CAFs) that radically influence the disease progression across many cancers, including the colorectal cancer (CRC). In theory, targeting CAFs holds great potential in optimizing CRC treatment. However, attempts to translate the therapeutic benefit of CAFs into clinic practice face many obstacles, largely due to our limited understanding of the heterogeneity in their origins, functions, and mechanisms. In recent years, accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 155 publications
(169 reference statements)
1
29
0
Order By: Relevance
“…High amounts of lactic acid secreted by CAFs with an upregulated expression of MCT4 as an energy substrate are absorbed by cancer cells, and these participate in the metabolic alteration of cancer cells, thereby enhancing tumor malignancy. In the present study, the western blotting results showed that the expression levels of α-SMA and FAP, the two most widely used markers for identifying CAFs ( 41 , 42 ), were upregulated in HIFs after co-culture. Moreover, the results from the immunofluorescence staining experiments confirmed the upregulation of α-SMA and FAP, and a narrower, longer and spindle-shaped morphology of the cells was observed in the induced CAFs that was similar to that commonly exhibited in activated fibroblasts, as one of their characteristic features in CAFs ( 43 ).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…High amounts of lactic acid secreted by CAFs with an upregulated expression of MCT4 as an energy substrate are absorbed by cancer cells, and these participate in the metabolic alteration of cancer cells, thereby enhancing tumor malignancy. In the present study, the western blotting results showed that the expression levels of α-SMA and FAP, the two most widely used markers for identifying CAFs ( 41 , 42 ), were upregulated in HIFs after co-culture. Moreover, the results from the immunofluorescence staining experiments confirmed the upregulation of α-SMA and FAP, and a narrower, longer and spindle-shaped morphology of the cells was observed in the induced CAFs that was similar to that commonly exhibited in activated fibroblasts, as one of their characteristic features in CAFs ( 43 ).…”
Section: Discussionsupporting
confidence: 53%
“…Although the exact method of identifying CAFs is still controversial, it is generally hypothesized that CAFs are derived from activated myofibroblasts in the TME. The typical spindle-shaped morphology changes compared with quiescent fibroblasts, and the upregulation of several specific CAF markers that are widely used, such as α-SMA, FAP and IL-6, can be used to identify CAFs ( 41 - 43 ). Recently, co-culture with cancer cells has become a way to obtain and study CAFs in vitro ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated IL-8 expression changes the tumor microenvironment in favor of metastasis through increasing neutrophil and tumor-associated macrophages' infiltration [110]. Additionally, recent studies suggest that cancer cells and CAFs can produce IL-8 to further promote growth and metastasis [111]. IL-8 is considered an independent adverse prognosis factor in colorectal carcinoma.…”
Section: Il-8mentioning
confidence: 99%
“…Myofibroblasts, cancer-associated fibroblasts (CAFs), and CSCs secrete a range of growth factors and signaling proteins such as the agonist Wnt3a and the antagonist Notum in the TME [ 24 , 165 ], both essential for canonical Wnt signaling transduction. Recently, a new mechanism for tumor resistance was proposed, suggesting that APC-deficient cell clones become “supercompetitive” through TME modulation, secreting Wnt antagonists such as Notum, which inhibit the survival of normal ISC neighboring cells, inducing their differentiation [ 79 , 80 , 81 ].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%